2013
DOI: 10.1038/nchembio.1403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive immune activation: glycosylation does matter

Abstract: Major histocompatibility complex (MHC) class I and II are glycoproteins that can present antigenic peptides at the cell surface for recognition and activation of circulating T lymphocytes. Here, the importance of the modification of protein antigens by glycans on cellular uptake, proteolytic processing, presentation by MHC and subsequent T-cell priming is reviewed. Antigen glycosylation is important for a number of diseases and vaccine design. All of the key proteins involved in antigen recognition and the orc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
226
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(230 citation statements)
references
References 110 publications
2
226
0
2
Order By: Relevance
“…N-and O-linked glycans carried by cell surface glycoproteins and glycolipids are involved in different physiological or pathological processes, such as host defense, immunological and inflammatory responses, tissue homeostasis or cancers 6,7 . In particular, carbohydrates participate to multiple mechanisms of cellular regulation including intracellular trafficking, endocytosis, folding and proteolysis, cell communication, regulation of signaling pathways, as well as cell differentiation, adhesion and growth 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…N-and O-linked glycans carried by cell surface glycoproteins and glycolipids are involved in different physiological or pathological processes, such as host defense, immunological and inflammatory responses, tissue homeostasis or cancers 6,7 . In particular, carbohydrates participate to multiple mechanisms of cellular regulation including intracellular trafficking, endocytosis, folding and proteolysis, cell communication, regulation of signaling pathways, as well as cell differentiation, adhesion and growth 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation of protein glycosylation has been recognized as a strategy to promote antigen internalization and antigen presentation via MHC class I and class II molecules promoting cellular and humoral immune responses (44). Targeting the mannose receptor, a C-type lectin, showed that mannosylation provided an efficient strategy to improve antigen uptake, processing, and presentation.…”
mentioning
confidence: 99%
“…that can promote uptake of antigens, such as dendritic cells (45)(46)(47)(48)(49). It is known that HA from viruses that are adapted to circulate in humans contains more glycosylation sites in the globular head domain compared to avian HA (44).…”
Section: Discussionmentioning
confidence: 99%